Strategic Implementation of OneStream Systems: Identifying and Prioritizing User-Centric Criteria - Prabowo, Ery Restu; Putro, Utomo Sarjono (International Journal of Entrepreneurship and Sustainability Studies, 2023)
This research explores the implementation of OneStream, a sophisticated software platform used in financial planning and reporting, within an organization. It emphasizes a thorough internal and external analysis to evaluate the organization's resources and capabilities, and to understand the external factors influencing the adoption of OneStream. The internal analysis identifies strengths such as technical expertise and a skilled workforce, and weaknesses including insufficient training and limitations in OneStream's utilization. The external analysis uncovers opportunities like market growth and strategic partnerships, alongside threats from competition and global economic uncertainties. Data collection involved in-depth interviews with six OneStream experts, followed by a detailed Analytic Hierarchies Process (AHP) for quantitative analysis. The findings reveal key factors influencing OneStream implementation, categorized under Security and Reliability, Accuracy and Data Integration, Efficiency and Performance, and Ease of Use. AHP results indicate a lower consensus in Security and Reliability than expected, with System Reliability and Availability emerging as critical. Accuracy and Data Integration show a moderate consensus, emphasizing the importance of Data Accuracy. Based on these analyses, three strategic pathways for advancing OneStream usage are proposed: preserving the status quo, refining and enhancing OneStream, and integrating OneStream with other systems. The research concludes that integration is the most preferred solution, receiving the highest preference in the AHP analysis. This strategy involves not only technical adjustments but also organizational developments, particularly within the Capital Accounting Administration, to ensure effective integration and collaboration. This study provides valuable insights for organizations considering similar technology adoption, balancing the preservation of foundational principles with embracing technological innovations for sustainable growth and efficiency.